The epithelial sodium channel in inflammation and blood pressure modulation - Ahmad, Taseer; Ertuglu, Lale A.; Masenga, Sepiso K.; Kleyman, Thomas R.; Kirabo, Annet (Frontiers in Cardiovascular Medicine, 2023)
The epithelial sodium channel (ENaC) is a key modulator of blood pressure and volume homeostasis in the kidney. ENaC is composed of alpha(α)/beta(β)/gamma(γ) or delta(δ)/beta(β)/gamma(γ) subunits. The δ subunit is functional in the guinea pig, but not in routinely used experimental rodent models including rat or mouse, and thus remains the least understood of the four subunits. While the δ-ENaC subunit is poorly expressed in the human kidney, we recently found that its gene variants are associated with blood pressure and kidney function. All four subunits are expressed in the human vasculature where ENaC influences vascular function. Moreover, we recently found that δ-ENaC, together with the other three ENaC subunits, are also expressed in human antigen presenting cells (APCs), where ENaC may influence vascular function, immune cell activation and blood pressure. In this review, we highlight recent findings on the role of extrarenal ENaC in inflammation and blood pressure regulation, emphasizing where δ-ENaC may be targeted to provide new drug therapies for hypertension.